Comparative plastome analysis of Musaceae and new insights into phylogenetic relationships - Fu, Ning; Ji, Meiyuan; Rouard, Mathieu; Yan, Hai-Fei; Ge, Xue-Jun (Springer, 2022)
Musaceae is an economically important family consisting of 70-80 species. Elucidation of the interspecific relationships of this family is essential for a more efficient conservation and utilization of genetic resources for banana improvement. However, the scarcity of herbarium specimens and quality molecular markers have limited our understanding of the phylogenetic relationships in wild species of Musaceae. Aiming at improving the phylogenetic resolution of Musaceae, we analyzed a comprehensive set of 49 plastomes for 48 species/subspecies representing all three genera of this family.